IET Conference Publications 2009
DOI: 10.1049/cp.2009.0652
|View full text |Cite
|
Sign up to set email alerts
|

New network design standards for the grid connection of large concentrations of distributed generation

Abstract: Connecting large concentrations of Distributed Generation to the distribution networks usually requires high investments in network extension. This contribution describes how Enexis used its Risk Based Asset Management approach to develop new network design standards for the grid connection of large concentrations of DG in a cost-effective way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…These advanced methods are especially necessary in cases with high uncertainties and large investment consequences. For example, in cases like [6], where scenarios with large concentrations of distributed generation has let to huge network investments, but utilization of new assets failed to happen due to changing scenario conditions. Appropriate network planning tools are necessary to deal with these kinds of challenges in future distribution networks.…”
Section: Requirements For Future Network Planning (Tools)mentioning
confidence: 99%
“…These advanced methods are especially necessary in cases with high uncertainties and large investment consequences. For example, in cases like [6], where scenarios with large concentrations of distributed generation has let to huge network investments, but utilization of new assets failed to happen due to changing scenario conditions. Appropriate network planning tools are necessary to deal with these kinds of challenges in future distribution networks.…”
Section: Requirements For Future Network Planning (Tools)mentioning
confidence: 99%
“…Some time ago Enexis has, based on its risk-based asset management (RBAM) methodology, investigated which of the solutions were most effective and gave the largest risk reduction [6]. In the analysis it was concluded that both using the spare transformer and the application of FCLs result in only a limited risk reduction.…”
Section: Comparison Of Solutionsmentioning
confidence: 99%
“…The past few years distributed generation (DG) in the Netherlands has increased and it now has a significant influence on design and operation of distributon networks [1,2]. This paper focuses on how the presence of DG in the medium voltage (MV) grid influences the powerflow from the high voltage (HV) grid to the MV-grid.…”
Section: Introductionmentioning
confidence: 99%